Stakeholder Engagement in a Sustainable Circular Economy Theoretical and Practical Perspectives - Kujala, Johanna; Heikkinen, Anna; Blomberg, Annika (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
The purpose of this open access edited collection is to discuss the role and importance of stakeholder engagement in a sustainable circular economy from multiple theoretical and practical perspectives. Developing and maintaining a circular economy is an essential step to a more environmentally friendly and socially inclusive society. In addition to redesigning products and business models to minimise waste and increase the reuse of materials, a transition towards a sustainable circular economy requires collaboration and co-operation between various stakeholders from all parts of society. An international team of contributors explore how stakeholder engagement can foster and support sustainable change, assessing current literature and laying out guidance for future study. The collection is of interest to academics and students of sustainability management and sustainable business models, stakeholder theory and practice, and the circular economy. Johanna Kujala is a Professor of Management and Organizations and Vice Dean for Research at the Tampere University, Faculty of Management and Business, Finland. Her current research interests focus on stakeholder theory and engagement, sustainable value-creation and circular economy, and corporate responsibility and business ethics. Anna Heikkinen is an Adjunct Professor, Senior Lecturer of Management and Organizations, and the Academic Director of the Responsible Business Master's degree programme at the Tampere University, Faculty of Management and Business, Finland. Her research is primarily in the areas of stakeholder theory and corporate responsibility and sustainability, examining the relationships between business organisations and society. Annika Blomberg is a Senior Research Fellow at the Tampere University, Faculty of Management and Business, Finland. Her research topics include stakeholder engagement, collaboration and ethics and she is interested in critical approaches as well as aesthetically sensitive and language-focused methods. Johanna Kujala is Professor of Management and Organizations and Vice Dean for Research at the Tampere University, Faculty of Management and Business, Finland. Her current research interests focus on stakeholder theory and engagement, sustainable value creation and circular economy, and corporate responsibility and business ethics. Anna Heikkinen is Adjunct Professor, Senior Lecturer of Management and Organizations, and the Academic Director of the Responsible Business Master's degree programme at the Faculty of Management and Business, Tampere University, Finland. She is internationally well-connected Scholar, whose research is primarily in the areas of stakeholder theory and corporate responsibility and sustainability, examining the relationships between business organisations and society. Annika Blomberg is Post-doctoral Researcher at the Faculty of Management and Business, Tampere University, Finland. Her research topics include stakeholder engagement, collaboration, and ethics, and she is interested in critical approaches as well as aesthetically sensitive and language-focussed methods. .